XXV Interregional Festival “Zodchestvo in Siberia” - Grigoryeva, Elena (project baikal, 2025)
Founded at the very beginning of the millennium, “Zodchestvo in Siberia” (ZVS) has been held in Irkutsk for many years. Following the model of the Moscow Festival “Zodchestvo”, rules were laid down for review competitions, stars of Russian architecture were invited, sometimes foreign architects also participated, and hot topics were discussed at the round table of the House of Architects. The author’s guided tours presented new objects to the guests and Irkutsk residents. A trip to Lake Baikal traditionally concluded the program. In 2014, ZVS venue moved to Krasnoyarsk for the first time, and in 2017 Krasnoyarsk hosted ZVS for the second time. In the same year, we received an offer from Altai architects to hold the next festival in Barnaul. It was decided to keep the usual abbreviation, filling it with a new geographical meaning. The next festival, “Zodchestvo in Siberia 2019”, was hosted by Tomsk. The 20th anniversary was held in Irkutsk, the homeland of the festival. Then there were Kemerovo in 2021, Novosibirsk in 2022, Irkutsk again in 2023, and in 2024 Krasnoyarsk hosted ZVS for the third time. The 25th anniversary festival “Zodchestvo in Siberia” returns to its birthplace – Irkutsk. The organizers filled the program with surprises and innovations. Project Baikal, as always, publishes a catalog of participants’ works, a complete list of participants and a brief chronicle of the competition. EG, founder of the festival